1997
DOI: 10.1007/s002239900211
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Among Bone Mineral Density, Broadband Ultrasound Attenuation, Mechanical Indentation Testing, and Bone Orientation in Bovine Femoral Neck Samples

Abstract: Broadband ultrasound attenuation (BUA) of the calcaneus has been found to correlate with bone mineral density (BMD) of the femoral neck. The purpose of this study was to determine if a correlation exists among femoral neck BUA, femoral neck BMD, and incremental indent depth, a qualitative indicator of local mechanical bone strength, in bovine samples, and if this correlation is dependent upon orientation. For 12 of the bovine samples obtained, BUA was measured at the femoral neck and was followed by a BMD dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…QUS is in¯uenced by trabecular orientation and may thus represent`bone quality' (Glu È er et al, 1993;Stewart et al, 1994;Hans et al, 1995b;Langton et al, 1996;Njeh et al, 1996;Duquette et al, 1997), but the de®nite proof hereof is not yet available. Thus, QUS probably mainly re¯ects BMD, but many investigations indicate that QUS measures something other than bone density alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…QUS is in¯uenced by trabecular orientation and may thus represent`bone quality' (Glu È er et al, 1993;Stewart et al, 1994;Hans et al, 1995b;Langton et al, 1996;Njeh et al, 1996;Duquette et al, 1997), but the de®nite proof hereof is not yet available. Thus, QUS probably mainly re¯ects BMD, but many investigations indicate that QUS measures something other than bone density alone.…”
Section: Resultsmentioning
confidence: 99%
“…Studies with orthogonal measurements on cubes of bovine trabecular bone have shown that BUA and UVB (ultrasound velocity through bone) depend on trabecular orientation (Glu È er et al, 1993;Njeh et al, 1996;Duquette et al, 1997). Glu È er et al (1993) found that BUA was about 50% larger when measured along the axis of the compressive trabeculae compared with the two perpendicular axes, even though BMD was the same in all directions.…”
Section: Bone Quantity or Quality?mentioning
confidence: 99%
“…Abhängigkeiten zwischen der Knochenmineraldichte und der mechanischen Festigkeit des spongiösen Knochens wurden bereits im Schenkelhals des Schweins [15], der humanen Wirbelsäule [16] und in der Metaphyse von langen Röhrenknochen [9,10] nachgewiesen. Saitoh et al [4] führten ebenso mechanische Untersuchungen in 3 Höhen des proximalen Humerus parallel zum Collum anatomicum durch und fanden die höchste Festigkeit im kranialen, dorsalen Aspekt des proximalen Humerus.…”
unclassified
“…Furthermore, the different site of measure can play an important role in the comparison of our results. According to recent studies [27,28,29] there is disparity between central and peripheral measurements. It is estimated, for example, that 20±30 % of individuals have normal US values of the calcaneus but have low axial BMD.…”
Section: Discussionmentioning
confidence: 99%